Response of Helenium amarum to Environmental Stressors in the Presence of Mycorrhizal Fungi and Its Role as a Pollinator Resource - Austin Jameson; Lisa Horth (International Journal of Plant Biology)
Globally, climate change is causing shifts in precipitation patterns. Shifting precipitation patterns can be a stressor for many species. One species that is experiencing such stress is Helenium amarum Raf (H. Rock). H. amarum, thrives in dry upland pastures and low-lying grassy and sandy habitat in the mid-Atlantic (USA), where it persists despite storm-driven standing water. Helenium amarum is a species that is toxic to livestock and has been found outside its native range. Temperature and light impacts on germination are already known, but the role of water availability and potential ameliorating effects of mycorrhizae during water stress have not been studied. We planted seeds collected from nature in the Aquatics Facility at Old Dominion University under varied water regimes (drought, flood, intermediate) and evaluated supplemental mycorrhizal fungi impacts on plant traits. Plants in soil with supplemental mycorrhizae grew to nearly twice the height of ‘no supplement’ controls (<semantics><mover accent="true">x¯</mover></semantics>mycorrhizae = 23.16, S.D. = 7.33 cm; <semantics><mover accent="true">x¯</mover></semantics>control = 13.70, S.D. = 6.33 cm; p < 0.001). Leaf length was also greater with supplemental mycorrhizae ( <semantics><mover accent="true">x¯</mover></semantics>mycorrhizae = 3.52, S.D. = 1.27 cm; <semantics><mover accent="true">x¯</mover></semantics>control = 2.66, S.D. = 0.75 cm; p = 0.0239). Leaf number was greater in high water treatments, with supplemental mycorrhizae (high-water: <semantics><mover accent="true">x¯</mover></semantics>mycorrhizae = 27.47, S.D. = 10.66; <semantics><mover accent="true">x¯</mover></semantics>control = 13.50, S.D. = 6.80; p < 0.001; pulse-water <semantics><mover accent="true">x¯</mover></semantics>mycorrhizae = 30.50, S.D. = 8.64; <semantics><mover accent="true">x¯</mover></semantics>control = 22.38, S.D. = 7.42; p = 0.0254). This work demonstrates that H. amarum tolerates both dry and moist soil during germination, which may be relevant for successful invasiveness. Supplemental mycorrhizal fungi buffer the effects of water stress, which is significant as climate change impacts precipitation. Additionally, we have documented that pollinators frequently visit flowers of the plant, which is indicative that the species provides ecosystem services in the form of pollinator resources.